Professionalism and competencies as predictors of public relations practitioners self-efficacy: a conceptual framework - Gusau, Ahmed Lawal; Abdullah, Zulhamri; Mohd Hasan, Nurul Ain; Tamam, Ezhar (Academic Hosting & Event Management Solutions, 2018)
The essence of this research work is to test the predictive roles of attitudinal professionalism and competencies in public relations practitioners’ self-efficacy. For the fast three (3) decades, a lot of works have been conducted by scholars as part of an effort to uplift PR as a full pledge profession. However, scholars still lament the shortfall of PR practitioners in the discharge of their professional duties. This work is an attempt to study public relations practitioners’ ability in accomplishing professional tasks which self-efficacy represents. The work conceptualizes Six (6) PR self-efficacy dimensions and also tests the predictive role of attitudinal professionalism; which is practitioners’ commitment to their profession and competencies; which represents sets of behaviors that are required to accomplish organizational objectives. It appraises the importance of commitment to professional development and mastering professional competencies that are evolving and changing. Conceptualizing the dimension of PR self-efficacy remains the originality of this work.